What Are Models of Care? A Systematic Search and Narrative Review to Guide Development of Care Models for Premature Ovarian Insufficiency - Jones, Alicia R.; Tay, Chau T.; Melder, Angela; Vincent, Amanda J.; Teede, Helena (Seminars in Reproductive Medicine, 2020)
No specific model of care (MoC) is recommended for premature ovarian insufficiency (POI), despite awareness that POI is associated with comorbidities requiring multidisciplinary care. This article aims to explore the definitions and central components of MoC in health settings, so that care models for POI can be developed. A systematic search was performed on Ovid Medline and Embase, and including gray literature. Unique definitions of MoC were identified, and thematic analysis was used to summarize the key component of MoC. Of 2,477 articles identified, 8 provided unique definitions of MoC, and 11 described components of MoC. Definitions differ in scope, focusing on disease, service, or system level, but a key feature is that MoC is operational, describing how care is delivered, as well as what that care is. Thematic analysis identified 42 components of MoC, summarized into 6 themes—stakeholder engagement, supporting integrated care, evidence-based care, defined outcomes and evaluation, behavior change methodology, and adaptability. Stakeholder engagement was central to all other themes. MoCs operationalize how best practice care can be delivered at a disease, service, or systems level. Specific MoC should be developed for POI, to improve clinical and process outcomes, translate evidence into practice, and use resources more efficiently.
Keywords: premature ovarian insufficiency; care model; healthcare delivery; healthcare systems; quality improvement